Structure–Activity Relationship of Terpenes with Anti‐Inflammatory Profile – A Systematic Review - Santana Souza, Marilia Trindade; Almeida, Jackson Roberto Guedes da Silva; Souza Araujo, Adriano Antunes; Duarte, Marcelo Cavalcante; Gelain, Daniel Pens; Moreira, José Cláudio Fonseca; Santos, Marcio Roberto Viana; Quintans‐Júnior, Lucindo José (Basic & clinical pharmacology & toxicology, 2014)
Inflammation is a complex biological response that in spite of having available treatments, their side effects limit their usefulness. Because of this, natural products have been the subject of incessant studies, among which the class of terpenes stands out. They have been the source of study for the development of anti‐inflammatory drugs, once their chemical diversity is well suited to provide skeleton for future anti‐inflammatory drugs. This systematic review reports the studies present in the literature that evaluate the anti‐inflammatory activity of terpenes suffering any change in their structures, assessing whether these changes also brought changes in their effects. The search terms anti‐inflammatory agents, terpenes, and structure–activity relationship were used to retrieve English language articles in SCOPUS, PUBMED and EMBASE published between January 2002 and August 2013. Twenty‐seven papers were found concerning the structural modification of terpenes with the evaluation of anti‐inflammatory activity. The data reviewed here suggest that modified terpenes are an interesting tool for the development of new anti‐inflammatory drugs.